2018
DOI: 10.1128/jb.00395-18
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation by Restriction Modification Systems Affects the Global Transcriptome Profile in Borrelia burgdorferi

Abstract: Prokaryote restriction modification (RM) systems serve to protect bacteria from potentially detrimental foreign DNA. Recent evidence suggests that DNA methylation by the methyltransferase (MTase) components of RM systems can also have effects on transcriptome profiles. The type strain of the causative agent of Lyme disease,Borrelia burgdorferiB31, possesses two RM systems withN6-methyladenosine (m6A) MTase activity, which are encoded by thebbe02gene located on linear plasmid lp25 andbbq67on lp56. The specific … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 85 publications
(111 reference statements)
1
26
0
Order By: Relevance
“…Of the m6A modifications called at RM sites, 4.9% of sites were called as m6A modified in less than 50% of sequencing reads, 23.7% of sites were called as modified in between 50–75% of sequencing reads, and finally 71.4% of sites were called as modified at greater than 75% of aligned reads. Previous studies have also reported heterogeneity in the frequency of SMRT sequencing reads with base modifications; it has been hypothesized that these differences are due to timing in DNA replication and subsequent methylation [3335]. Whether there is a temporal component accounting for the heterogeneity in m6A DNA modifications, and whether this impacts other functions of m6A modifications, such as in influencing gene transcription in S .…”
Section: Resultsmentioning
confidence: 99%
“…Of the m6A modifications called at RM sites, 4.9% of sites were called as m6A modified in less than 50% of sequencing reads, 23.7% of sites were called as modified in between 50–75% of sequencing reads, and finally 71.4% of sites were called as modified at greater than 75% of aligned reads. Previous studies have also reported heterogeneity in the frequency of SMRT sequencing reads with base modifications; it has been hypothesized that these differences are due to timing in DNA replication and subsequent methylation [3335]. Whether there is a temporal component accounting for the heterogeneity in m6A DNA modifications, and whether this impacts other functions of m6A modifications, such as in influencing gene transcription in S .…”
Section: Resultsmentioning
confidence: 99%
“…MTase BCAL3494 was specifically linked to methylation of the CACAG motif, and MTase BCAM0992 was linked to methylation of the GTWWAC motif. This strategy of DNA methylation analysis, in which the methylome of strains lacking MTases is determined, has been used in various bacteria, as it is an effective way to find associations between predicted MTases and genome-wide methylation motifs (39,40). For example, several methylation motifs were identified in Burkholderia pseudomallei, including motifs CA-CAG and GTWWAC (41).…”
Section: Discussionmentioning
confidence: 99%
“…The combined characterization of the methylome and transcriptome in wild-type and methyltransferase-defective mutant cells revealed that DNA methylation also impacts gene expression patterns in the pathogenic bacteria Vibrio cholera (Chao et al, 2015) and Helicobacter pylori (Estibariz et al, 2019). In Borrelia burgdorferi DNA methylation through the natural RM system also impacts the global transcriptome (Casselli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%